A new insight into the formation of β-crystals of isotactic polypropylene induced by zinc dicarboxylic acids. (2nd December 2022) - Zhang, Xixiang; Qin, Wei; Wu, Tong; Zhao, Shicheng
Abstract: Some zinc dicarboxylic acids can induce numerous β-crystals formation in isotactic polypropylene (iPP), thus improving the crystallization behavior and mechanical properties of iPP. However, the corresponding nucleation mechanism of β-crystals remains inadequate, leading to the absence of a theoretical basis for the design and preparation of new and high-efficiency β-nucleating agents (β-NAs). In this work, we demonstrate a new mechanism that β-crystals can be formed when the interfacial interaction between β-NAs and iPP is comparable to that between β-PP and iPP. The interfacial interaction occurs when iPP epitaxially crystallizes on the NA surface, which will affect the folding and arrangement of iPP chains, thereby leading to formation of different crystalline forms of iPP. The interaction energy of iPP chain with α-PP and β-PP is used as a judgment criterion, which is resolved by molecular dynamics (MD) simulation. We surprisingly found that when the interaction energy of NA/iPP was close to that of β-PP/iPP, the NA can be acted as β-NA; β-crystals were inclined to form when the interaction energy of NA/iPP was close to that of β-PP/iPP. Furthermore, the simulation results are well verified by the crystallization behavior of iPP in the presence of aromatic zinc dicarboxylic acids of zinc terephthalate (ZnCC1) and zinc 4-carboxybenzoate (ZnCC2), lending strong support to the proposed nucleation mechanism and method. This work proposes a new insight into the formation of β-crystals of iPP based on the interaction energy of NA and iPP, and demonstrates a method to rapidly predict and evaluate the β-nucleation effect of NAs, thus may serve as a theoretical guidance for the design of NAs that can induce iPP with specific crystalline forms. Graphical abstract: Image 1 Highlights: The single crystals of zinc dicarboxylic acids were systematically cultured and single crystal structures were obtained. The effects of single crystals on the isothermal crystallization behavior of iPP were observed. A new simulation method is proposed to predict and evaluate the effect of NA on the crystallization behavior of iPP.